Absolute and Conditional Convergence: Definition, Examples

A series ∑an is called absolutely convergent if ∑|an| converges. A series ∑an is called conditionally convergent if it converges but not absolutely. In this article, we study absolute and conditional convergence with their definitions and examples.

Absolutely Convergent Series

Definition: A series $\displaystyle \sum_{n=1}^\infty a_n$ is called absolutely convergent if the series $\displaystyle \sum_{n=1}^\infty |a_n|$ is convergent.

For example, the series $1-\dfrac{1}{2^2}+\dfrac{1}{3^2}-\dfrac{1}{4^2}+\cdots$ is an absolutely convergent series.

An absolutely convergent series is convergent. That is, if a series converges absolutely then it also converges. But, the converse is not true, that’s where the concept of conditionally convergent series comes into the picture.

Conditionally Convergent Series

Definition: A series $\displaystyle \sum_{n=1}^\infty a_n$ is called conditionally convergent (or semi-convergent) if the series is convergent but not absolutely.

For example, the series $1-\dfrac{1}{2}+\dfrac{1}{3}-\dfrac{1}{4}+\cdots$ is a conditionally convergent series.

Questions and Answers

Q1: Show that the series $1-\dfrac{1}{2^2}+\dfrac{1}{3^2}-\dfrac{1}{4^2}+\cdots$ is absolutely convergent.

The series ∑an = $\displaystyle \sum_{n=1}^\infty (-1)^{n+1} \dfrac{1}{n^2}$.

Now, ∑|an| = $\displaystyle \sum_{n=1}^\infty |(-1)^{n+1} \dfrac{1}{n^2}|$ = $\displaystyle \sum_{n=1}^\infty \dfrac{1}{n^2}$. This is a p-series with p=2>1; hence ∑|an| is convergent.

Therefore, the given series is absolutely convergent.

Q2: Show that the series $1-\dfrac{1}{3}+\dfrac{1}{5}-\dfrac{1}{7}+\cdots$ is conditionally convergent.

Step 1: (To show the series converges)

The series = ∑ (-1)n+1an = $\displaystyle \sum_{n=1}^\infty (-1)^{n+1} \dfrac{1}{2n-1}$.

Thus, an = $\dfrac{1}{2n-1}$. Now, we have:

1. $\dfrac{1}{2n-1} >0$ for all n=1,2,3,… That is, an > 0 ∀ n.
2. an – an+1

= $\dfrac{1}{2n-1} – \dfrac{1}{2(n+1)-1}$

= $\dfrac{2n+1-2n+1}{(2n-1)(2n+1)}$

= $\dfrac{2}{(2n-1)(2n+1)}$ > 0 ∀ n.

So, an – an+1 > 0 ∀ n.
This shows that {an} is monotonically decreasing.
3. limn→∞ an = limn→∞ $\dfrac{1}{2n-1}$ = 0.

So by Leibnitz’s test, the given series converges.

Step 2: (To show the series is not absolutely convergent)

Now, we will show that this series does not converge absolutely.

The series of absolute terms is given by $1+\dfrac{1}{3}+\dfrac{1}{5}+\dfrac{1}{7}+\cdots$ = $\displaystyle \sum_{n=1}^\infty x_n$, where xn = $\dfrac{1}{2n-1}$.

We use the limit comparison test with the series ∑ yn = ∑ 1/n. Now,

limn→∞ (xn/yn)

= limn→∞ $\dfrac{n}{2n-1}$

= limn→∞ $\dfrac{1}{2-\frac{1}{n}}$ (dividing top and bottom by n)

= 1/2, which is finite and positive.

Thus, by limit form of comparison test, both ∑ 1/n and ∑ 1/(2n-1) behave similarly. We know ∑ 1/n diverges by p-series as p=1. Hence, the series ∑ 1/(2n-1) also diverges.

Therefore, the given series is absolutely convergent and hence by definition conditionally convergent.

Q3: Show that the series $1-\dfrac{1}{2}+\dfrac{1}{3}-\dfrac{1}{4}+\cdots$ is conditionally convergent.

Step 1: (To show the series is not absolutely convergent)

The series = ∑ an = $\displaystyle \sum_{n=1}^\infty (-1)^{n+1} \dfrac{1}{n}$.

Note that ∑ |an| = $\displaystyle \sum_{n=1}^\infty \dfrac{1}{n}$ is not convergent by p-series as p=1.

So the series is not absolutely convergent.

Step 2: (To show the series converges)

The series converges by Leibnitz’s test. The proof is here.

Therefore, by definition, the given series is conditionally convergent.

Also Study:

FAQs

Q1: What is an absolutely convergent series?

Answer: A series ∑an is said to be absolutely convergent if ∑|an| converges. The series 1-1/22+1/32-1/42+… converges absolutely.

Q2: What is an conditionally convergent series?

Answer: If a series ∑an converges but not absolutely, then it is said to be conditionally convergent. The series 1-1/2+1/3-1/4+… converges conditionally.

Share via: